2021
DOI: 10.4329/wjr.v13.i5.137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of point and two-dimensional shear wave elastography of the spleen in healthy subjects

Abstract: BACKGROUND Few systematic comparative studies of the different methods of physical elastography of the spleen are currently available. AIM To compare point shear wave and two-dimensional elastography of the spleen considering the anatomical location (upper, hilar, and lower pole). METHODS As part of a prospective clinical study, healthy volunteers were examined for splenic elasticity using four different ultrasound devices between May 2015 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…Albayrak et al used SWE and reported that SS did not differ according to sex and age [10]. Several other studies are also in agreement with these findings showing a lack of relationship between ultrasonography-measured SS and age and sex [2,21,36,37]. Despite these findings, the results of our study are of interest since it is the first study that included only healthy volunteers and was conducted using 3T MRE.…”
Section: Discussionsupporting
confidence: 87%
“…Albayrak et al used SWE and reported that SS did not differ according to sex and age [10]. Several other studies are also in agreement with these findings showing a lack of relationship between ultrasonography-measured SS and age and sex [2,21,36,37]. Despite these findings, the results of our study are of interest since it is the first study that included only healthy volunteers and was conducted using 3T MRE.…”
Section: Discussionsupporting
confidence: 87%
“…Albayrak et al used SWE and reported that SS did not differ according to sex and age [10]. Several other studies are also in agreement with these findings showing a lack of relationship between ultrasonography-measured SS and age and sex [2,21,36,37]. Despite these findings, the results of our study are of interest since it is the first study that included only healthy volunteers and was conducted using 3T MRE.…”
Section: Discussionsupporting
confidence: 87%
“…Previously published results demonstrated a variability of stiffness results depending on the location of ARFI investigation in the spleen [25]. Therefore, we performed ARFI SSM measurements at three defined areas in the spleen (Figure 4) both at baseline and follow-up visits and compared the values obtained in these regions with the SSM values for the whole spleen: ARFI values for the upper (2.55 m/s) and bottom sections (3.59 m/s) of the spleen differed significantly from the SSM results of the whole spleen (3.00 m/s, p = 0.00007 and p = 0.00008, respectively).…”
Section: Resultsmentioning
confidence: 94%
“…The difference between our study and the study of Kim et al and the other studies investigating spleen stiffness may be explained by the way elastography evaluation of the spleen was performed: in the previous studies, delta-SSM values were not evaluated examining spleen stiffness repetitively on the same region of the spleen, but on different spots at the baseline and follow-up investigations. However, in a recently published study, a significant variation of results for spleen ARFI elastography was demonstrated depending where and how a "region of interest" is placed [25]. The results of ARFI performance can significantly vary dependent on the upper, hilar, or bottom third of the spleen investigated.…”
Section: Discussionmentioning
confidence: 99%